PENGARUH EMPLOYEE STOCK OWNERSHIP PROGRAM TERHADAP KINERJA PERUSAHAAN PUBLIK DI BURSA EFEK INDONESIA - Hartono, Agus; Wibowo, Alexander Jatmiko (Faculty of Economics Universitas Atma Jaya Yogyakarta, 2014)
The study aims to analyze the diferences between the company’s performance before and after the adoption of an Employee Stock Ownership Program. Te research sample using public companies that has made an Employee Stock Ownership Program in 2004-2012. Research using variable proftability ratios, activity ratios, solvability ratio, liquidity ratio as an indicator of observations on the performance of the company, as well as the hypothesis test (Paired Sample t-test) to examine the diferences in performance of the company before and after the adoption of an Employee Stock Ownership Program. The results showed that there was no signifcant diference between the performance of the company before and after the adoption of the ESOP.Key words : Employee Stock Ownership Program, company performance.